2001
DOI: 10.1111/j.1574-6941.2001.tb00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal communities in two disparate deteriorated ancient wall paintings: detection, identification and temporal monitoring by denaturing gradient gel electrophoresis

Abstract: In the present study we describe the detection of Archaea in two different deteriorated ancient wall paintings, located in Austria and Spain, under different humidity/salinity regimes and climates. Archaeal communities were analyzed by combination of denaturing gradient gel electrophoresis (DGGE) of PCR‐amplified DNA encoding 16S rRNA and the construction of clone libraries. DGGE analysis was used for temporal monitoring of the archaeal communities as well as for screening of the clone libraries. Selected clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
(63 reference statements)
0
23
0
Order By: Relevance
“…The closest match to clone byn3-12 (Fig. 2e) was Halobacterium clone K14 (AM159641) isolated from the mural paintings on the deteriorated ancient wall surface [28], whereas the closest match to clone byn5-30 (Fig. 2e) was Uncultured archaeon clone 371 (EF188566) isolated from the “white colonizations” on the paleolithic paintings, Altamira Cave, Spain [29].…”
Section: Resultsmentioning
confidence: 99%
“…The closest match to clone byn3-12 (Fig. 2e) was Halobacterium clone K14 (AM159641) isolated from the mural paintings on the deteriorated ancient wall surface [28], whereas the closest match to clone byn5-30 (Fig. 2e) was Uncultured archaeon clone 371 (EF188566) isolated from the “white colonizations” on the paleolithic paintings, Altamira Cave, Spain [29].…”
Section: Resultsmentioning
confidence: 99%
“…Schabereiter-Gurtner et al [19] [20] described a basic molecular protocol for the study of microbial communities colonizing cultural assets based on the sequences of the small subunit (16S for prokaryotes and 18S for eukaryotes) ribosomal RNA (rRNA) genes. Since then, many authors have used and further developed molecular protocols for the study of microbial communities colonising art works and monuments [21] [22] [23] [24] [25]. Nevertheless, it is worth noting that the best choice is the combination of classical cultivation techniques and molecular methods for the detection of the whole (cultivable and non-cultivable) microbial community in a sample.…”
Section: Introductionmentioning
confidence: 99%
“…In this study seven (4.4%) 16S rDNA sequences that were related to the mentioned works were found. Finally eight sequences (5%) were related to four different historical locations, which partly also showed the pink pigmentation phenomenon: the church of Saint Anna im Feld, Germany [17], the Roman Necropolis of Carmona, Spain [14], [29], [34], the Tomb of the Monkeys, Italy [35] and an old mould-damaged building [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that ancient stone works and mural paintings represent a common habitat for extremely salt tolerant and moderate halophilic bacteria [10][13] and archaea [10], [14]. The rosy discolouration of stone works in different historical buildings located in various parts of Europe was also already subject of different studies [3], [15][17].…”
Section: Introductionmentioning
confidence: 99%